2016
DOI: 10.1080/02687038.2016.1186265
|View full text |Cite
|
Sign up to set email alerts
|

Which treatment outcomes are most important to aphasia clinicians and managers? An international e-Delphi consensus study

Abstract: Background: Clinicians have expressed frustration at the lack of strong evidence for aphasia treatments. Inconsistent outcome measurement practices across treatment trials have negatively impacted the quality and strength of evidence for aphasia interventions. Core Outcome Sets (COSs; minimum sets of outcomes/outcome measures) are increasingly being used to maximise the quality, relevancy, transparency, and efficiency of health treatment research. The current study is the third in a trilogy of stakeholder pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…A recent international study of aphasia clinicians and managers revealed consensus that dyadic communication, that is, the ability of both the person with aphasia and CP to communicate with each other, was the most agreed treatment outcome of aphasia rehabilitation (Wallace, Worrall, Rose, & LeDorze, 2016b). It is possible that clinicians perceive it to be efficient to work jointly with clients and their CPs.…”
Section: Delivering Conversation Therapymentioning
confidence: 99%
“…A recent international study of aphasia clinicians and managers revealed consensus that dyadic communication, that is, the ability of both the person with aphasia and CP to communicate with each other, was the most agreed treatment outcome of aphasia rehabilitation (Wallace, Worrall, Rose, & LeDorze, 2016b). It is possible that clinicians perceive it to be efficient to work jointly with clients and their CPs.…”
Section: Delivering Conversation Therapymentioning
confidence: 99%
“…Further stakeholder perspectives are needed to gain a comprehensive picture of important outcomes from aphasia treatments. Accordingly two further studies have been conducted examining clinician (Wallace, Worrall, Rose, and Le Dorze, 2016a).and reseracher perspectives on treatment outcomes (Wallace, Worrall, Rose, and Le Dorze, 2016b). This information will be paired with a systematic review and meta-analysis of outcome measures in a final consensus process to develop a COS for aphasia treatment research.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Further stakeholder perspectives are needed to gain a comprehensive picture of important outcomes from aphasia treatments. Accordingly two further studies have been conducted examining clinician (Wallace, Worrall, Rose, and Le Dorze, 2016a).and researcher perspectives on treatment outcomes (Wallace, Worrall, Rose, and Le Dorze, 2016b). This information will be paired with a systematic review and meta-analysis of outcome measures in a final consensus process to develop a COS for aphasia treatment research.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Classification of outcomes using the common metric of the ICF was used to enable the comparison of results from this study, with the results from other participant groups within the ROMA project (Wallace, Worrall, Rose, & Le Dorze, 2016a;Wallace, Worrall, Rose, Le Dorze, et al, 2016b). ICF linking rules developed by Cieza and associates (2002;, and…”
Section: Roundmentioning
confidence: 99%
See 1 more Smart Citation